Cut-Off Low (DANA) in Valencia: Visual Representation of Death and Grief in Photojournalism - Morcate, Montse; Pardo Sainz, Rebeca (Media and Communication, 2026)
This article examines front-page images from a selection of newspapers portraying the loss of life, grief, and destruction caused by the cut-off low that hit the Valencian community, Spain, on 29 October 2024. This climate-related disaster was the first national catastrophe to take place since Covid-19 and resulted in at least 237 fatalities, leaving a devastated social and physical landscape. The research analyses images from a selection of regional, national, and international newspapers in the first few weeks following this disaster, examining graphic portrayals of the dead, the recovery of bodies, scenes of people in grief, and other unsettling images to explore possible underlying narratives, biases, and absences. The framework follows previous research on images of the Covid-19 pandemic in relation to ethics and the current context of instant image sharing, the effects of globalization, and the contemporary practices connected to the visibilization of death which vary depending on the nature of the crisis and the relationship to those affected. This article aims to contribute to broader discussions on the ethics of visual representation and the construction of meaning in times of crisis.
Keywords: climate-related disaster; death; flood; grief; news images; newspapers; photojournalism; Spain